Eorðscræf, eglond and iscealdne sæ: Landscape, Literalism and Metaphor in Some Old English Elegies - Tedford, Margaret (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Abstract: This article explores the depictions of landscape in the Old English elegies The Wife’s Lament, Wulf and Eadwacer, The Wanderer and The Seafarer. For many years scholars have debated how to interpret these depictions and have been deeply divided over whether landscape is to be understood literally or metaphorically in Old English poetry. This article reassesses these poems to argue for a more complex interaction between the literal and fi gurative aspects of landscape setting than has thus far been appreciated. Keywords: landscape, Old English poetry, The Wife’s Lament, Wulf and Eadwacer, The Wanderer, The Seafarer, isolation.